Implementation of The Problem Based Learning Model in The Mathematics Learning Material Operations Counting Whole Numbers in Sixth Grade Elementary School - Moch Nurhadi (Papanda Journal of Mathematics and Science Research, 2023)
This Study aimed tell implementation of Problem Based Learning. This learning model was to the improvement of students learning outcomes by counting whole numbers in sixth-grade Elementary Schools in the Gajah Mada Cluster, Dempet District, Demak Regency. This study used the descriptive qualitative method with a place of research in sixth-grade Balerejo I Elementary School, in collecting data used observation, interview, and documentation. Data analysis used descriptive qualitative analysis. Based on the results of research conducted that the implementation of PBL learning models to increase student learning outcomes in the material for counting whole numbers in sixth-grade Elementary School staged in its learning activities. Conclusion in the implementation, it was known that students were more creative and enthusiastic in the process of learning Mathematics, material operations, and counting numbers, and student learning outcomes increased quite high.